Pengaruh Servant Leadership Dan Komunikasi Terhadap Kinerja Karyawan Pada PT Kranji Jaya Abadi - Zauharah Ramdona (Global Leadership Organizational Research in Management, 2024)
PT Kranji Jaya Abadi is a leader in the construction industry with a major speciali-zation in infrastructure development and large-scale commercial projects. In em-ployee performance efforts, the role of servant leadership and communication is very important, because both are key parts to create a comfortable work environ-ment and produce quality Human Resources (HR). The purpose of this study is to analyze the influence of servant leadership and communication on the performance of PT Kranji Jaya Abadi employees. Especially to find out how much each of these independent variables contributes to employee performance. The method used in this study is a quantitative method with a statistical approach with data processing using SPSS 22. Data was collected through observation and dissemination of ques-tionnaires involving 32 employees of PT Kranji Jaya Abadi. The results of the re-search on serviceleadership and communication were stated to have a positive and significant influence on the performance of the teachers. PT Kranji Jaya Abadi is expected to continue to develop and strengthen the practice of servant leadership and maintain good communication at all managerial levels. This is expected to im-prove overall employee performance and encourage the achievement of company goals.